Miggy and Tiggy : a book about overcoming jealousy - Waite, Michael P., 1960-; DeRosa, Tony (Elgin, Ill. : Chariot Books, 1987)
Tiggy uses his new puppy to make Miggy jealous, endangering their friendship and almost losing the puppy. Includes a related Bible verse.
13 23 36
Keywords: Dogs -- Fiction; Friendship -- Fiction; Christian life -- Fiction; Stories in rhyme; Jealousy -- Fiction